2010
DOI: 10.1007/s12257-009-3079-z
|View full text |Cite
|
Sign up to set email alerts
|

Toward advanced ionic liquids. Polar, enzyme-friendly solvents for biocatalysis

Abstract: Ionic liquids, also called molten salts, are mixtures of cations and anions that melt below 100 o C. Typical ionic liquids are dialkylimidazolium cations with weakly coordinating anions such as (MeOSO 3 ) or (PF 6 ). Advanced ionic liquids such as choline citrate have biodegradable, less expensive, and less toxic anions and cations. Deep eutectic solvents are also included in the advanced ionic liquids. Deep eutectic solvents are mixtures of salts such as choline chloride and uncharged hydrogen bond donors suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
159
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(168 citation statements)
references
References 100 publications
3
159
0
5
Order By: Relevance
“…[19][20][21][22] In addition, they act as solvents or catalysts for various organic reactions. 23,24 Similarly, RTILs with the hydroxyl groups have CO2 absorption, [25][26][27][28][29] and cellulose/protein dissolution abilities. [30][31][32] The catalytic behavior of RTILs in the organic reactions, for instance, the yield of the product, depends on the acid-base properties of RTILs.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] In addition, they act as solvents or catalysts for various organic reactions. 23,24 Similarly, RTILs with the hydroxyl groups have CO2 absorption, [25][26][27][28][29] and cellulose/protein dissolution abilities. [30][31][32] The catalytic behavior of RTILs in the organic reactions, for instance, the yield of the product, depends on the acid-base properties of RTILs.…”
Section: Introductionmentioning
confidence: 99%
“…By chemical modification of the polar or apolar components or charge of the ions, numerous ILs with a range of physicochemical properties such as viscosity, catalytic activity, or solvation can be generated. We now have task specific ionic liquids that can be applied for a range of designated applications [4,5]: ionic liquids as drugs [6,7], as batteries and super-capacitors for solving energy demands of the environment [8][9][10][11], to capture greenhouse gases, to dissolve proteins [12,13] and cellulose [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that chitin can be dissolved in some ILs The interaction of ionic liquids and enzymes are not well understood so far. It depends on several factors (Gorke et al, 2010;Mu et al, 2012) as the anion and cation of ionic liquid, its polarity, hydrophobicity/ hydrofilicity, viscosity, length of a chain substituting a central ring. It has been reported that ILs can increase or decrease the activity of enzyme as well as can be neutral.…”
Section: Introductionmentioning
confidence: 99%